PEMBELAJARAN GROUP TO GROUP EXCHANGE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Teguh Raharja (UNION: Jurnal Ilmiah Pendidikan Matematika, 2017)
The purpose of this study was to describe the process of learning mathematics with active learning methods of type Groupto Group Exchange. Group to Group Exchangeis able to increase motivation and learning outcomes in learning mathematic on VIIA class of MTsMa’arif Pekutan Kebumen. Type of this research is classroom action research. Subjects of this study were students of VIIA grade ofMTsMa’arif Pekutan Kebumen as many as 18 student. The object of this study are the motivation and learning outcomes of mathematics with mathematic a llearning method Group to Group Exchange (GGE). The results showedthat the motivation and learning outcomes has increased. This is shown by an increase in the average of motivation percentage of students for each cycle. In the precycle average of student motivation in precentage is 61.40%, and increased to 70.19% in the first cycle. Then in the second cycle increased again became 80.28%. the average of student learning out comeson the precycle is 64.50 with average of completeness 38.88% from 18 students. On the first cycle increased to 73.61 with average of completeness 66.67% and than on the second cycles increased to78.08 with average of completeness 83.33%.